Ethics and autonomous weapons - Leveringhaus, Alex (Palgrave pivot, 2016)
Written by a political philosopher at the forefront of the autonomous weapons debate, the book clearly assesses the ethical and legal ramifications of autonomous weapons, and presents a novel ethical argument against fully autonomous weapons.